Gain-of-function mutations in the calcium channel CACNA1C (Cav1.2) cause non-syndromic long-QT but not Timothy syndrome. (March 2015) - Wemhöner, Konstantin; Friedrich, Corinna; Stallmeyer, Birgit; Coffey, Alison J.; Grace, Andrew; Zumhagen, Sven; Seebohm, Guiscard; Ortiz-Bonnin, Beatriz; Rinné, Susanne; Sachse, Frank B.; Schulze-Bahr, Eric; Decher, Niels
Abstract: Gain-of-function mutations in CACNA1C, encoding the L-type Ca 2 + channel Cav1.2, cause Timothy syndrome (TS), a multi-systemic disorder with dysmorphic features, long-QT syndrome (LQTS) and autism spectrum disorders. TS patients have heterozygous mutations (G402S and G406R) located in the alternatively spliced exon 8, causing a gain-of-function by reduced voltage-dependence of inactivation. Screening 540 unrelated patients with non-syndromic forms of LQTS, we identified six functional relevant CACNA1C mutations in different regions of the channel. All these mutations caused a gain-of-function combining different mechanisms, including changes in current amplitude, rate of inactivation and voltage-dependence of activation or inactivation, similar as in TS. Computer simulations support the theory that the novel CACNA1C mutations prolong action potential duration. We conclude that genotype-negative LQTS patients should be investigated for mutations in CACNA1C, as a gain-of-function in Cav1.2 is likely to cause LQTS and only specific and rare mutations, i.e. in exon 8, cause the multi-systemic TS. Highlights: Screening 540 patients we identified six LQT syndrome mutations in CACNA1C . All these mutations caused a gain-of-function combining different mechanisms. Computer simulations confirm action potential prolongation by the novel mutations. Gain-of-function in Cav1.2 is likely to cause non-syndromic LQTS not Timothy syndrome. Genotype-negative LQTS patients should be investigated for mutations in CACNA1C .